(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2018)
In Southkhali Union of Bagerhat district in Bangladesh about 47% of the total population is living beyond the service area of cyclone shelters (CS) not only for the carrying capacity of CS but also for the accessibility. Location-allocation tool of Network Analyst tool in ArcGIS determined the service area of each CS in the study area based on its shelter capacity and accessibility. People residing outside the service area of cyclone shelter are highly vulnerable due to low elevation of land and poor housing structure. The location-allocation tool of Network Analyst provided the proper evacuation plan that would identify the shelter location for each household or cluster of population and the evacuation route also. It would also help to find the proper location to build new shelters for unserved community. Asiat. Soc. Bangladesh, Sci. 44(2): 137-148, December 2018